2006
DOI: 10.1021/pr060112a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Application of Sodium Deoxycholate to Proteomic Analysis of Rat Hippocampal Plasma Membrane

Abstract: Detergents have been widely used for the solubilization of membrane proteins and the improvement of their digestion. In this paper, we have evaluated the application of sodium deoxycholate (SDC) to the solubilization and digestion of rat hippocampal plasma membrane (PM) proteins. For in-solution digestion, rat hippocampal PM fraction from sucrose-density gradient centrifugation was solubilized by boiling in 1.0% SDC, and directly digested without dilution. During the in-gel digestion of the hippocampal PM prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 28 publications
(52 reference statements)
3
102
1
Order By: Relevance
“…Furthermore, because SDC precipitates at low pH, it can be removed from the digests by centrifugation following acidification prior to sample analysis, preventing any potential ion suppression Lin et al, 2010). In addition, Zhou et al (2006) also demonstrated that during in-gel digestion the addition of 0.1% SDC in the buffer could remarkably enhance the coverage of tryptic peptides and the number of hydrophobic membrane proteins identified.…”
Section: On-membrane Digestionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, because SDC precipitates at low pH, it can be removed from the digests by centrifugation following acidification prior to sample analysis, preventing any potential ion suppression Lin et al, 2010). In addition, Zhou et al (2006) also demonstrated that during in-gel digestion the addition of 0.1% SDC in the buffer could remarkably enhance the coverage of tryptic peptides and the number of hydrophobic membrane proteins identified.…”
Section: On-membrane Digestionmentioning
confidence: 99%
“…However, sodium deoxycholate (SDC) was found to be compatible with trypsin activity, with enzyme activity not being significantly influences by concentrations up to 2% Lin et al, 2008). Zhou et al (2006) evaluated the use of SDC in place of 0.1% SDS for on-membrane digestion of rat hippocampal plasma membrane fraction as assessed by MALDI-TOF MS and CapLC-MS/MS. The use of SDC resulted in more total membrane protein identifications (71 vs. 31) and more integral membrane proteins (IMPs) (50 vs. 22) by CapLC-MS/MS.…”
Section: On-membrane Digestionmentioning
confidence: 99%
“…The sequential double Lys--C/trypsin digestion has been recently shown to be more efficient in generating fully cleaved peptides than tryptic digest alone [30] and is therefore recommended for all protein samples analyzed by LC--MS. Sodium deoxycholate is one of a few LC--MS compatible detergents, since it precipitates after acidification [25,33,38] using 2M HCl to a final concentration of 50mM and can then be easily removed by centrifugation at 10,000g for 15min before LC--MS analysis. All peptide samples were then desalted by C18 reversed--phase spin columns according to the manufacturer's instructions (Macrospin, Harvard Apparatus), separated in aliquots of 25 ug peptides, dried under vacuum and stored at --80ÂșC until further use.…”
Section: Cell Lysis and Proteolysismentioning
confidence: 99%
“…The most popular materials of bipolar plates, besides graphite, are metallic materials or composites based on carbon: carboncarbon composites [25,26], carbon-polymer composites [27], and carbon coated metal [27][28][29][30]. Metallic bipolar plates provide many advantages such as cheaper material cost, high thermal and electrical conductivity, variety of manufacturing processes and excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%